Emergence of antibiotic resistant bacteria from coastal environment - a review - Khan Chowdhury, Ahmed Jalal; John, Akbar; Yunus, Kamaruzzaman; K., Kathiresan (InTech, 2012)
1. Introduction Antibiotic resistance in microbes is a growing issue of human health. The extraordinary ability of microbes to develop resistance to various antibiotics attracted evolutionary scientists and environmental biologists in recent years. Historically, the use of antimicrobial agents started in 1904 with the discovery of Tripan red by Ehrlich and Shiga (Browning & Gulbransen, 1936). In 1929, penicillin was discovered by Alexander Fleming when his group found that the fungus Penicilium notatum produces a very selective inhibitor for Staphylococcus sp. Fleming’s discovery showed that not only synthetic agents like Ehrlich’s “Magic Bullet” but also a microbial product can be an effective antimicrobial drug (Hare, 1970). In 1943, Waksman started to use the word “antibiotics” when he discovered streptomycin (Wainwright, 1988). After the initial age of discovery and since the 1970s many antimicrobial agents have been developed together with the discoveries of new antibiotics. It is well documented that the evolution of antibiotic resistance in bacterial strains is a direct consequence of natural selection applied by widespread use of antibiotic drugs (Benveniste & Davies, 1973). The providential experiment by Fleming demonstrated the production of antibiotics (Penicillin) which eventually led to its large-scale production from mold Penicillium notatum in the 1940s. As early as the late 1940s resistant strains of bacteria began to appear due to their extraordinary ability in gaining resistance towards any particular antibiotics with elapsing generation (Shoemaker et al., 2001; Chopra & Roberts et al., 2001; Doern et al., 2001). In 1980 it was estimated that 3–5% of S. pneumoniae were penicillin-resistant and by 1998, 34% of the S. pneumoniae sampled were resistant to penicillin. Currently, it is estimated that more than 70% of the bacteria that cause hospitalacquired infections are resistant to at least one of the antibiotics used to treat them (NIAID, 2006).